2014
DOI: 10.1155/2014/485687
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fibrinogen with Severity of Stable Coronary Artery Disease in Patients with Type 2 Diabetic Mellitus

Abstract: Background. Some studies have suggested a relation of plasma fibrinogen to the severity of coronary artery disease (CAD). However, whether plasma fibrinogen can predict the presence and severity of CAD in patients with diabetes mellitus has not been determined. Methods. A total of consecutive 373 diabetic patients with typical angina pectoris who received coronary angiography were enrolled and classified into three groups by tertiles of Gensini score (GS, low group <8; intermediate group 8~28; high group >28).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
(49 reference statements)
5
20
2
Order By: Relevance
“…Furthermore, our data suggested that a cut-off value of 3.21 g/L may be useful in predicting the severity of coronary stenosis. The findings were in consistent with previous studies among Western population [27] and our recent study in Chinese patients with CAD and diabetes mellitus [28] . However, those previous studies were limited by the lack of strict assessment system of coronary atherosclerosis or the relatively small sample size.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our data suggested that a cut-off value of 3.21 g/L may be useful in predicting the severity of coronary stenosis. The findings were in consistent with previous studies among Western population [27] and our recent study in Chinese patients with CAD and diabetes mellitus [28] . However, those previous studies were limited by the lack of strict assessment system of coronary atherosclerosis or the relatively small sample size.…”
Section: Discussionsupporting
confidence: 93%
“…[20][21][22] Many clinical studies have consistently shown elevated levels of fibrinogen in patients with cardiovascular disease and thrombosis. [23][24][25] The conventional test kits available in a hospital for plasma/ serum analysis suffer from long time delays for the availability of results due to the need of specialised laboratories, which may in turn delay the therapy, and prolong patient anxiety. The potential of vibrational spectroscopy techniques coupled with multivariate analysis techniques have been previously investigated for a range of clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, understanding its predictors would greatly aid in disease prevention and treatment, and the possible relationships between various plasma markers and CAD have intensively been investigated [2][3][4][5] . Among these markers, endothelin 1 (ET-1) has been demonstrated to play a role in endothelial dysfunction and inflammation 6) , both of which are actively involved in the pathophysiology of the onset and progression of CAD, from the formation of atherosclerotic plaque to the development of acute coronary syndrome (ACS) and heart failure following myocardial infarction 7) .…”
Section: Introductionmentioning
confidence: 99%